Fecal Microbiota Transplantation Ameliorates Active Ulcerative Colitis by Downregulating Pro-inflammatory Cytokines in Mucosa and Serum - Zhang, Wen-Hui; Jin, Ze-Yu; Yang, Zhong-Hua; Zhang, Jia-Yi; Ma, Xiao-Han; Guan, Jing; Sun, Bao-Lin; Chen, Xi (Frontiers in Microbiology, 2022)
AIM To explore the short and long-term efficacy and safety of fecal microbiota transplantation (FMT) and its mechanism in UC treatment. METHODS Thirty active UC patients were enrolled and FMT was administered with the first colonoscopy and two subsequent enema/transendoscopic enteral tubing practical regimens in the First Affiliated Hospital of Anhui Medical University in China. Disease activity and inflammatory biomarkers were assessed 6 weeks/over 1 year after treatment. The occurrence of adverse events was also recorded. The samples from blood and mucosa were collected to detect the changes of inflammatory biomarkers and cytokines. The composition of gut and oral microbiota were also sampled and sequenced to confirm the alteration of microbial composition. RESULTS Twenty-seven patients completed the treatment, among which 16 (59.3%) achieved efficacious clinical response and 11 (40.7%) clinical remission. Full Mayo score and calprotectin dropped significantly and remained stable over 1 year. FMT also significantly reduced the levels of CRP, IL-1β, and IL-6. The gut microbiota altered significantly with increased bacterial diversity and decreased metabolic diversity in responsive patients. The pro-inflammatory enterobacteria decreased after FMT, and the anti-inflammatory Collinsella increased. Accordingly, the altered metabolic functions including antigen synthesis, amino acids metabolism, short chain fatty acid production, and vitamin K synthesis of microbiota were also corrected by FMT. CONCLUSION FMT seems to be safe and effective for active UC patients who are nonresponsive to mesalazine or prednisone in the long-term. FMT could efficiently downregulate pro-inflammatory cytokines to ameliorate the inflammation.